2001
DOI: 10.1128/jvi.75.6.2929-2937.2001
|View full text |Cite
|
Sign up to set email alerts
|

Linkage between STAT Regulation and Epstein-Barr Virus Gene Expression in Tumors

Abstract: Epstein-Barr virus (EBV) latency gene expression in lymphoblastoid cell lines is regulated by EBNA2.However, the factors regulating viral expression in EBV-associated tumors that do not express EBNA2 are poorly understood. In EBV-associated tumors, EBNA1 and frequently LMP1 are synthesized. We found that an alternative latent membrane protein 1 (LMP1) promoter, L1-TR, located within the terminal repeats is active in both nasopharyngeal carcinoma and Hodgkin's disease tissues. Examination of the L1-TR and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
137
2
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(145 citation statements)
references
References 62 publications
(71 reference statements)
5
137
2
1
Order By: Relevance
“…The suitability of this strategy is further supported by the fact that, in addition to their presence in lymphocytes ( Figure 1D), constitutively activated STATs are also noted in other nontumour cells ( Figure 1C). A recent study found persistent STAT1, STAT3 and STAT5 activation in NPC tissue (Chen et al, 2001). However, insufficient data have been reported to provide an overall picture of the expression of these STATs in NPC.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The suitability of this strategy is further supported by the fact that, in addition to their presence in lymphocytes ( Figure 1D), constitutively activated STATs are also noted in other nontumour cells ( Figure 1C). A recent study found persistent STAT1, STAT3 and STAT5 activation in NPC tissue (Chen et al, 2001). However, insufficient data have been reported to provide an overall picture of the expression of these STATs in NPC.…”
Section: Discussionmentioning
confidence: 97%
“…In a recent study, the JAK/STAT pathway was shown to play a role in maintaining in vivo latency of EBV (Chen et al, 1999). Aberrant STAT activation has also been proposed as a necessary and predisposing event for EBV-driven tumorigenesis in immunocompetent individuals (Chen et al, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…LMP-1 can be expressed from two alternative promoters: the EBNA-2-responsive ED-L1 or the promoter located in the first terminal repeat (TR-promoter) (14). Two binding sites for the STAT transcription factors were identified in the LMP-1 promoters (one in each) (15). Furthermore, STAT3, activated by IL-6, was shown to activate the TR LMP-1 promoter in epithelial cells (16,17).…”
mentioning
confidence: 99%
“…The second gene cluster (brown cluster), overexpressed in nodular sclerosis GOHD, contained many cytokine genes, reÂŻecting the presence of high amounts of cytokines released within the tumour tissue. It also included genes involved in signal transduction in response to virtually all types of stimuli transmitted by cytokines and antigen receptors, such as STAT3, previously shown to be activated in H/RS cells (Chen et al, 2001), and MAP2K6 (Stein et al, 1996). Altogether, these data suggest an intense tra cking of intercellular signals between neoplastic and reactive cells within GOHD tissues, which may have a favourable inÂŻuence on the outcome by contributing to regulate tumour growth.…”
Section: Discussionmentioning
confidence: 74%